2022
DOI: 10.3390/ma15092971
|View full text |Cite
|
Sign up to set email alerts
|

Friction Stir Spot Welding of Different Thickness Sheets of Aluminum Alloy AA6082-T6

Abstract: Friction stir spot welding (FSSW) is one of the important variants of the friction stir welding (FSW) process. FSSW has been developed mainly for automotive applications where the different thickness sheets spot welding is essential. In the present work, different thin thickness sheets (1 mm and 2 mm) of AA6082-T6 were welded using FSSW at a constant dwell time of 3 s and different rotation speeds of 400, 600, 800, and 1000 rpm. The FSSW heat input was calculated, and the temperature cycle experience during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…In papers [ 17 , 18 ], the authors focused on selection of the parameters in friction stir spot-welding (FSSW) processes. Ataya et al [ 17 ] joined a low-carbon steel sheet (A283M-Grade C) with a brass sheet (CuZn40) by means of FSSW using different rotational speeds and dwell times to explore the effective range of parameters, enabling joints to be obtained with a high load-carrying capacity.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In papers [ 17 , 18 ], the authors focused on selection of the parameters in friction stir spot-welding (FSSW) processes. Ataya et al [ 17 ] joined a low-carbon steel sheet (A283M-Grade C) with a brass sheet (CuZn40) by means of FSSW using different rotational speeds and dwell times to explore the effective range of parameters, enabling joints to be obtained with a high load-carrying capacity.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…The authors also revealed that when the number of revolutions per spot ranged from 250 to 500, it was possible to produce joints with a high load-carrying capacity from 4 kN to 7.5 kN. In turn, in work [ 18 ], FSSW was used to join AA6082-T6 aluminium alloy sheets. Sheets with thicknesses of 1 mm and 2 mm were welded using different rotation speeds, while the dwell time was constant in all the variants.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…Hence, calculation of σ 2 is needed to determine the dispersal of outcomes in the distribution. Variance for the WSM and WPM can be calculated using Equations ( 4) and (5), respectively, and is shown in Table 5 [31][32][33]. For WSM:…”
Section: 𝑥 =mentioning
confidence: 99%
“…During stirring, the temperature of the workpiece material rises due to friction, and reaches a value where the workpiece becomes soft and plastically deformed. When this process is ideally employed, the mixing of the workpiece material takes place without any significant change in its phase and microstructure, proving that the process is a solid-state joining process [5]. This can be attributed to the fact that the melting of the material leads to coarsening of the grains as grain boundaries break down during melting, and when the material cools down, those grains combine to form bigger grains, affecting the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on this issue in the literature have used aluminum sheets with a thickness of 2 mm or greater [3]. There have been few studies on the welding of thinner plates through using FSSW method [4]. For this reason, the welding of thin aluminum alloy sheets with a thickness of less than 2 mm using the FSSW method were investigated in this study.…”
mentioning
confidence: 99%